ANALISIS STRUCTURE, CONDUCT AND PERFORMANCE INDUSTRI MEDIA CETAK SURAT KABAR HARIAN DI KOTA PEKANBARU - Fadila Fitriyani; Syafril Basri; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted to determine the structure of the market in the daily newspaper industry in Pekanbaru, knowing how the behavior of corporate firms in the industry and the company's performance in maintaining its presence in the newspaper industry amid electronic competition. This research method is quantitative descriptive. As this study used secondary data and primary data obtained from the United Company Press Pekanbaru city and obtained directly from industry respondents daily newspapers in Pekanbaru. The population of the daily newspaper industry in Pekanbaru totaling 20 companies. The analysis tool used is Market Share, Concentration Ratio Herfindahl Index-Hircsman, Capital to Labour Ratio and Price Cost Margin. Results from this study showed that by calculating the appropriate range CR4 and IHH acquired the daily newspaper industry market structure in Pekanbaru is the structure of monopolistic competition with the CR4 value of 33.44% and a value of 582.5 IHH. CLR industry behavior seen from the results showed that the CLR is only around 1.5% - 4% this means that the behavior of the daily newspaper industry in Pekanbaru is a labor-intensive industry. As for the performance of the daily newspaper industry in Pekanbaru city as seen from PCM gained an average of 53.69%. With most valued PCM 65,68% but did not become the largest market share (MS). This means that the benefits seen from PCM is not affected by market share.Keywords : structure, conduct, performance, daily newspaper industry